Report on research, innovation and technological performance in Germany 2020 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2020)
[Foreword ...] The Commission of Experts has selected the following topics for the five chapters of its current Annual Report: In chapter A 1, the Commission of Experts acknowledges measures taken by the Federal Government last year to implement the High-Tech Strategy 2025. Two new instruments of research and innovation policy have been created with the introduction of tax incentives for research and the establishment of the Federal Agency for Disruptive Innovation. Implementation of the Artificial Intelligence Strategy has begun and should be pursued vigorously. In 2019, the Federal Government and the Länder reached important agreements in the field of science policy, and these are discussed in chapter A 2. The Commission of Experts supports the increased importance being assigned to the transfer of knowledge and technology in the fourth Pact for Research and Innovation. It welcomes the fact that the 'Contract on the Future Strengthening of Studying and Teaching' was concluded for an unlimited period. However, the Commission of Experts warns against allowing the number of permanent non-professorial academic employment relationships to grow disproportionately when implementing the Contract on the Future. To mark the 30th anniversary of German reunification, in chapter B 1 the Commission of Experts examines the innovation activities of companies in east and west Germany, taking structural differences into account. The result is that the innovation activities of east German companies have converged with that of west German companies. However, they are still behind when it comes to launching innovation activities or introducing innovations to the market. The Commission of Experts recommends that companies not engaging in research and development should be more closely integrated into research and innovation funding and supported in bringing innovations to market. In chapter B 2, the Commission of Experts analyses the relationship between cybersecurity and innovation. This reveals that cyber threats have a negative impact on corporate innovation activities. Furthermore, cybersecurity is itself the subject of innovation activities. Measured in terms of the number of patent applications, Germany is a long way behind the USA, China and Japan. In particular, the Federal Government should promote the teaching of cybersecurity skills, secure digital infrastructures, promote R&I activities in cybersecurity, and support small and medium-sized enterprises in implementing cybersecurity measures. In chapter B 3, the Commission of Experts examines the exchange of knowledge and technology between Germany and China. There is concern in Germany that knowledge and technology exchange with China will lead to a one-sided outflow of know-how and thus weaken Germany's scientific and economic performance. In order to prevent this happening, the Federal Government should work to achieve a level playing field in direct investment, examine takeovers in the field of sensitive technologies more carefully, and improve overall knowledge about China in Germany.
Keywords: 330